Dual-action of thermoresponsive gels containing DsiRNA-loaded gold nanoparticles for diabetic wound therapy: Characterization, in vitro safety and healing efficacy - Ahmad Yasser Hamdi Nor Azlan; Haliza Katas; Nur Hamizah Habideen; Mohd Fauzi Mh Busra (Elsevier, 2020)
Diabetic wounds are difficult to treat due to multiple causes, including reduced blood flow and bacterial infections. Reduced blood flow is associated with overexpression of prostaglandin transporter (PGT) gene, induced by hyperglycaemia which causing poor vascularization and healing of the wound. Recently, gold nanoparticles (AuNPs) have been biosynthesized using cold and hot sclerotium of Lignosus rhinocerotis extracts (CLRE and HLRE, respectively) and capped with chitosan (CS) to produce biocompatible antibacterial nanocomposites. The AuNPs have shown to produce biostatic effects against selected gram positive and negative bacteria. Therefore, in this study, a dual therapy for diabetic wound consisting Dicer subtract small interfering RNA (DsiRNA) and AuNPs was developed to improve vascularization by inhibiting PGT gene expression and preventing bacterial infection, respectively. The nanocomposites were incorporated into thermoresponsive gel, made of pluronic and polyethylene glycol. The particle size of AuNPs synthesized using CLRE (AuNPs-CLRE) and HLRE (AuNPs-HLRE) was 202 ± 49 and 190 ± 31 nm, respectively with positive surface charge (+30 to + 45 mV). The thermoresponsive gels containing DsiRNA-AuNPs gelled at 32 ± 1 °C and released the active agents in sufficient amount with good texture and rheological profiles for topical application. DsiRNA-AuNPs and those incorporated into thermoresponsive pluronic gels demonstrated high cell viability, proliferation and cell migration rate via in vitro cultured cells of human dermal fibroblasts, indicating their non-cytotoxicity and wound healing properties. Taken together, the thermoresponsive gels are expected to be useful as a potential dressing that promotes healing of diabetic wounds.